2016
DOI: 10.1093/humrep/dew280
|View full text |Cite
|
Sign up to set email alerts
|

No increased risk of major congenital anomalies or adverse pregnancy or neonatal outcomes following letrozole use in assisted reproductive technology

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 23 publications
2
38
1
3
Order By: Relevance
“…Although an association between the use of letrozole for infertility treatment and congenital anomalies was reported in a relatively small number of pregnancies, such an association was rejected in recent studies . In general, letrozole 2.5 or 5 mg per day was used for ovarian stimulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an association between the use of letrozole for infertility treatment and congenital anomalies was reported in a relatively small number of pregnancies, such an association was rejected in recent studies . In general, letrozole 2.5 or 5 mg per day was used for ovarian stimulation .…”
Section: Discussionmentioning
confidence: 99%
“…Although an association between the use of letrozole for infertility treatment and congenital anomalies was reported in a relatively small number of pregnancies, 19 such an association was rejected in recent studies. [20][21][22] In general, letrozole 2.5 or 5 mg per day was used for ovarian stimulation. 5,7 Although the difference in serum peak E2 level did not reach statistical significance, there was a trend in that serum peak E2 level was lower in the 5 mg compared to 2.5 mg group.…”
Section: Fps (N = 29) Lps (N = 21) Pmentioning
confidence: 99%
“…The data that were reported at the ASRM's annual meeting in 2005 suggested that letrozole is teratogenic; however, in a RCT that used letrozole for 900 women with unexplained fertility, there was no increase in the rate of major anomalies . A study of infertile Japanese women that compared the data between 3136 natural cycles and 792 letrozole‐induced cycles, both of which were associated with fresh, single‐embryo transfer and resulted in a clinical pregnancy, revealed that the risk of miscarriage was, in fact, significantly lower in the letrozole group, while the two groups were equal in terms of major congenital anomalies and the risk for any specific organ system …”
Section: Recent Issues In Assisted Reproductive Technology For Fertilmentioning
confidence: 99%
“…35 A study of infertile Japanese women that compared the data between 3136 natural cycles and 792 letrozole-induced cycles, both of which were associated with fresh, single-embryo transfer and resulted in a clinical pregnancy, revealed that the risk of miscarriage was, in fact, significantly lower in the letrozole group, while the two groups were equal in terms of major congenital anomalies and the risk for any specific organ system. 36 Few studies have compared the treatment outcomes between controlled ovarian stimulation combined with letrozole and conventional controlled ovarian stimulation. In one such study that compared 142 cycles, in which letrozole was combined with a GnRH antagonist protocol, to 97 cycles conducted with a typical GnRH antagonist protocol, the number of oocytes that was retrieved was significantly lower in the former group despite equal doses of FSH preparations.…”
Section: Aromatase Inhibitors For Estrogen-dependent Malignanciesmentioning
confidence: 99%
“…Отмечено также, что применение летрозола в программах ВРТ обеспечивает сни-жение риска самопроизвольного прерывания беременности, не увеличивает риски серьезных врожденных аномалий и неблагоприятных пе-ринатальных исходов [58][59][60].…”
unclassified